(untitled) (Alternautas, 2023)
The leader of the Inga community shares some of the ideas behind the construction of an indigenous university in the Putumayo region of the Colombian Amazon. He also presents the book "Una Nueva Universidad Indígena en la Selva en Colombia" (A New Indigenous University in the Rainforest in Colombia).